Cultures et élevages de masse dans le contexte d'une écloserie-nurserie de mollusques bivalves : les productions phytoplanctoniques et le grossissement des post-larves - Le Borgne, Y.; Marin, J.; Vergonzanne, G. (Publications du Centre National pour l'Exploitation des Océans (CNEXO). Série : Actes de colloques, n° 7, 1979, pp. 105-154, 1979)
The hatchery-nursery from the Société Atlantique de Mariculture settled in Barfleur studied within the ECOTRON program set up by C.N.E.X.O. the characteristics of mass cultures for monospecific phytoplancton and of the rearing of oyster spat (Ostrea edulis. Crassostrea giqas) and clam spat (Venerupis semidecussata) . The maintenance features of the cultures in order to obtain cell densities around 1 million cell/ml. (or 50 g. of dry weight/m3) in containers up to 5000 liters have been established for the main species used in aquaculture (Isochrysis qalbana. Monochrysis lutheri, Tetraselmis suecica. Skeletonema costatum. Phaeodactylum tricornutum. Cyclotella nana, Chaetoceros calcitrans). The spat growth in nursery without providing any cultured food emphasized the benefit of the use of pond sea water instead of offshore sea water. The growth difference have been related to the variation in natural phytoplancton cell density. 5everal systems have been tested on newly set spat of Crassostrea qiqas in order to improve the rate of survival after metamorphosis. The combine use of a controlled environment in the hatchery and a continuous flow of water in an outside nursery for spat rearing gives a total rate of survival around 50 % among the animals obtained after setting. La société Atlantique de Mariculture dont l'écloserie- nurserie est implantée à Barfleur (Manche) a étudié dans le cadre du programme ECOTRON organisé par le C.N.E.X.O. les conditions de production de masse du phytoplancton en cultures monospécifiques et les conditions d'élevage des post-larves d'huîtres (Ostrea edulis. Crassostrea gigas) et de palourdes (Venerupis semidecussata). Les caractéristiques de maintenance des cultures en vue d'obtenir des densités de l'ordre du million de cellules algales par millilitre (ou 50 g. de poids sec/m3) en différents volumes jusqu'à 5000 litres ont été établies pour les principales espèces utilisées en aquaculture (Isochrysis qalbana. Monochrysis lutheri. Tetraselmis suecica, Skeletonema costatum, ...